Effects of high-intensity interval training under hypoxic conditions on energy system performance in collegiate football players - Dr. Jukdao Potisaen; Traimit Potisan; Supanithi Khumprommarach (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: High-Intensity Interval Training (HIIT) is widely recognized for enhancing athletic performance. However, whether simulated hypoxic conditions amplify the physiological effects of HIIT especially in sports like football that rely on multiple energy systems, remains underexplored.